The Impact of COVID-19 Pandemic on Patients Receiving Orthodontic Treatment - Shhabat, Zaid; Ghozlan, Mo'ath; Kana'an, Nadeem; Tashtoush, Ashraf; Alelaimat, Ayman; Saadeh, Rami (European Journal of Dentistry, 2022)
Objective The coronavirus disease 2019 (COVID-19) pandemic impacted the provision of dental treatment in a timely manner including orthodontic treatment. The objective of this study was to assess challenges encountered by patients undergoing orthodontic treatment during the pandemic and their attitude toward managing these challenges.Material and Methods A cross-sectional sample of orthodontic patients at Prince Rashid Hospital in the north of Jordan was recruited to participate in a self-administered questionnaire that included questions related to orthodontic problems encountered during the lockdown, ways to overcome these problems, and concerns about their treatment.Results A total of 120 patients participated, 40 males and 80 females. Most participants (n = 86) had a fixed orthodontic appliance, who reported various orthodontic problems (82%), but the most common problems reported were exposed wire endings and loosening of brackets. Likewise, the most commonly reported problem among those with removable appliances (n = 34) was a broken or loose appliance (60%). However, patients of both types of appliances ignored the problem and waited until the re-opening of dental offices. Further, most patients missed at least one appointment for different reasons and three-quarters of them (76.6%) did not communicate with their orthodontists during the lockdown. Patients expressed their disagreement with the closure of dental offices during the pandemic because of their concern of a prolonged waiting to receive another appointment.Conclusion The COVID-19 pandemic had a significant impact on orthodontic care and the maintenance of appointments during the lockdown periods. Patients varied in ways they managed their orthodontic problems, including their commitment to communicate with the dentists or maintain their appointments. Hence, patients should be trained on how to manage the appliance problems when they need and encourage them to accept distant communication during the emergencies.
Keywords: Jordan; COVID-19; Treatment; Orthodontic; Appointment; Lockdown